Sexual satisfaction, sexual compatibility, and relationship adjustment in couples: the role of sexual behaviors, orgasm, and men's discernment of women's intercourse orgasm - Klapilová, Kateřina; Brody, Stuart; Krejčová, Lucie; Husárová, Barbara; Binter, Jakub (The journal of sexual medicine, 2015)
INTRODUCTION: Research indicated that (i) vaginal orgasm consistency is associated with indices of psychological, intimate relationship, and physiological functioning, and (ii) masturbation is adversely associated with some such measures. AIM: The aim of this study was to examine the association of various dyadic and masturbation behavior frequencies and percentage of female orgasms during these activities with: (i) measures of dyadic adjustment; (ii) sexual satisfaction; and (iii) compatibility perceived by both partners. METHODS: In a sample of 85 Czech long-term couples (aged 20-40; mean relationship length 5.4 years), both partners provided details of recent sexual behaviors and completed sexual satisfaction, Spanier dyadic adjustment, and Hurlbert sexual compatibility measures. Multiple regression analyses were used. MAIN OUTCOME MEASURE: The association of sexual behaviors with dyadic adjustment, sexual compatibility, and satisfaction was analyzed. RESULTS: In multivariate analyses, women's dyadic adjustment is independently predicted by greater vaginal orgasm consistency and lower frequency of women's masturbation. For both sexes, sexual compatibility was independently predicted by higher frequency of penile-vaginal intercourse and greater vaginal orgasm consistency. Women's sexual satisfaction score was significantly predicted by greater vaginal orgasm consistency, frequency of partner genital stimulation, and negatively with masturbation. Men's sexual satisfaction score was significantly predicted by greater intercourse frequency and any vaginal orgasm of their female partners. Concordance of partner vaginal orgasm consistency estimates was associated with greater dyadic adjustment. CONCLUSIONS: The findings suggest that specifically penile-vaginal intercourse frequency and vaginal orgasm consistency are associated with indices of greater intimate relationship adjustment, satisfaction, and compatibility of both partners, and that women's masturbation is independently inversely associated with measures of dyadic and personal function. Results are discussed in light of previous research and an evolutionary theory of vaginal orgasm.
Keywords: Vaginal Orgasm; dospělí; Orgasm; Female; osobní uspokojení; Signal Detection, Psychological; Adult; Perception; ženské pohlaví; Vagina; orgasmus; Sexual Partners; sexuální partneři; interpersonální vztahy; percepce; lidé; Personal Satisfaction; teorie detekce signálu; Coitus; Sexual Intercourse; Sexual Behavior; sexuální chování; Masturbation; Male; Czech Republic; Relationship Satisfaction; Česká republika; Sexual Compatibility; Interpersonal Relations; mužské pohlaví; koitus; Dyadic Adjustment; masturbace; Sexual Satisfaction; vagina; Humans